OPTIMASI RESCHEDULE PEMBANGUANAN KAPAL KELAS 1 KENAVIGASIAN (KN. BACAN) DI ORELA SHIPYARD DENGAN LINIER PROGRAMING - Rosita Elen; Poernomo Heroe; Arumsari Nurvita (Politeknik Perkapalan Negeri Surabaya, 2018)
In a shipyard, shipbuilding process is inseparable from scheduling determined by the company. Although in the course of time a project usually meet obstacles in the process resulting on delays in building process and ship delivery. Pert Method (Project Evaluation Review Technique) is used in a project to find the critical path on network diagram in order to make time configuration becomes more effective. Furthermore crashing method is used by adding work hours to lessen lateness and excessive project cost. Duration accelerating used on critical path track, then cost minimilization and also linear programming time optimization completed by simplex approach on solver. The results obtained from time-planning calculation using network planning with Project Evaluation Review Technique (PERT) is applicable for the company on time and cost because the normal time which is 924 days could be crashed for 11 days into 913 days, increasing the efficiency on time and costs, the normal cost is about Rp Rp. 1,747,940,000 and the costs after crashing about Rp. 3,387,463,353. Results from Simplex LP (Linear Programming) for post-crashing duration is the optimum time because there is no change on solution’s solver in which the time is constant. The cost minimalization generated by simplex LP is Rp 6,046,912 day from crashed works. For a total duration of 11 days the minimum cost incurredis Rp. 66,516,03.